Case Report: Diffuse cerebral lymphomatosis with superimposed multifocal primary CNS lymphoma - Elizabeth Huai-Feng Li; Claire Davila; Connor Zuraski; Jennifer Chang; Vanessa Goodwill; Nikdokht Farid (Frontiers in Radiology)
DescriptionCerebral lymphomatosis (CL) is a rare subtype of primary central nervous system lymphoma (PCNSL). In CL, atypical lymphoid cells diffusely infiltrate the cerebral parenchyma without forming a discrete mass as seen with PCNSL. We report a case of a 66-year-old woman with diffuse CL and superimposed areas of PCNSL. She presented with subacute cognitive decline and weakness. CSF studies showed lymphocytosis and IL-10 elevation. She became increasingly somnolent despite steroid and intravenous immunoglobulin trials, and she succumbed to the disease four months after symptom onset.Radiologic findingsHer initial non-contrast head CT showed ill-defined hypodensities in the periventricular and subcortical white matter, bilateral basal ganglia, and central pons, which corresponded to diffuse T2/FLAIR hyperintensities on brain MRI. No abnormal enhancement, diffusion restriction, or discrete mass was present initially. Subsequently, MR spectroscopy demonstrated abnormally elevated choline:creatine and decreased NAA peaks, suggesting a hypercellular process. One month later, MRI revealed increasingly confluent T2/FLAIR hyperintensities with new diffusion restriction in the right caudate and left hippocampus, as well as new hyperperfusion in the right caudate. Again, no mass or enhancement was identified in these areas. On autopsy, parenchymal pathology was mostly consistent with CL. However, there were two areas of frank PCNSL in the right caudate and left hippocampus, which corresponded to the new areas of abnormality on her last MRI despite lacking the typical radiologic features of PCNSL.Novel aspectsThis is a unique case of CL with concurrent areas of PCNSL. Although CL is thought to be a distinct subtype of PCNSL, our case demonstrates that PCNSL may develop on a background of diffuse CL. In patients with subacute neurologic decline and MRI findings of diffuse leukoencephalopathy, diffuse CL should be considered.